ANALISA HUKUM ATAS TRANSAKSI GADAI SAHAM PERUSAHAAN PENANAMAN MODAL ASING DISERTAI PEMBERIAN KUASA ATAS SAHAM SEHUBUNGAN DENGAN LARANGAN PERJANJIAN PINJAM NAMA ATAU NOMINEE AGREEMENT DALAM UNDANG-UNDANG PENANAMAN MODAL - Richard C. Adam (Faculty of Law - Tarumanagara University, 2020)
Foreign investors as foriegn shareholders who plan to conduct a foreign direct investment in Indonesia often face the legal facts that there is a limitation of percentage of shares ownership in the joint venture company which will be established with the Indonesian shareholders. Foreign investors aim to manage or control the joint venture company since the foreign investor deemed as the party who knows the best of the management of the factory and the Indonesian shareholders only serve as legal formality in order to fulfill the requirement of establishment of the joint venture company. In the framework of complying with the said restriction of percentage of shares ownership then the foreign investor shall utilize the legal instrument such as nominee agreements in order to achieve the goals to control the joint venture company. Law Number 25 Year 2007 concerning Investment as amended by Law Number 11 Year 2020 concerning Works Creator has stipulated the restriction to foreign investors to make agreement or statement which states the shares ownership in the joint venture company is and on behalf of other persons. The objective of the said restriction is to eliminate the ownership of joint venture companies by the form of “de yure'' to be owned by a person but by the form of “de facto'' to be owned or at least to be possessed by another party.